Синергія логіки та штучного інтелекту: перетин світів у розвитку сучасних технологій - Милютін, О. Є. (ХНУРЕ, 2024)
This topic examines the interaction between two key areas - logic and artificial intelligence - aimed at achieving new levels of understanding and development of technologies. In particular, it explores the principles of formal and informal logic that form the basis for the development of algorithms and artificial intelligence models that can adapt to various situations and tasks. The analysis of this interaction helps to better understand how this synergy shapes future technological advances and promotes innovation in the field of artificial intelligence
Keywords: синергія; логіка